Pomegranate [videorecording (DVD)] - Namou, Weam; Rahmani, Sam; Shami, Zain; Taher, Ismail (Freestyle Digital Media, 2025)
It's the elections of Donald Trump in 2016, and a young, liberal, Iraqi Muslim refugee struggles to find her footing in a neighborhood of conservative, Iraqi Christians while battling her family's fears and demands of loyalty to traditions.